Gobernar lo sagrado: Articulaciones entre secularismo, religión y poder en Rusia - Vasquez, Gladys Angelica (Pontificia Universidad Católica del Perú, 2025)
This article analyzes how the Russian State, through religious nationalism and the doctrine of Russkiy Mir, constructs a political project that articulates sovereignty, identity, and moral order through the sacralization of State power. Using a critical discourse analysis of official, religious, and media sources, it examines the practices and narratives that produce a patriotic subjectivity based on fear, loyalty, and obedience. The results show that this alliance between the Kremlin and the Russian Orthodox Church legitimizes political actions, such as the war in Ukraine, under a spiritual rhetoric that strengthens social cohesion and consolidates an exclusive moral community. It is concluded that Russkiy Mir represents a post-secular form of modernity that employs the sacred as a technology of power to offer a political model alternative to secular liberalism.

El artículo analiza cómo el Estado ruso, a través del nacionalismo religioso y la doctrina del Russkiy Mir, construye un proyecto político que articula soberanía, identidad y orden moral mediante la sacralización del poder estatal. Utilizando un análisis crítico del discurso de fuentes oficiales, religiosas y mediáticas, se examinan las prácticas y narrativas que producen una subjetividad patriótica basada en el miedo, la lealtad y la obediencia. Los resultados muestran que esta alianza entre el Kremlin y la Iglesia ortodoxa legitima acciones políticas, como la guerra en Ucrania, bajo una retórica espiritual que fortalece la cohesión social y consolida una comunidad moral excluyente. Se concluye que el Russkiy Mir representa una forma postsecular de modernidad que utiliza lo sagrado como tecnología de poder para ofrecer un modelo político alternativo al liberalismo secular.
Governing the Sacred: Articulations between Secularism, Religion, and Power in Russia
Keywords: Secularism; Religious nationalism; Russkiy Mir; Public morality; Political subjectivation; Secularismo; Nacionalismo religioso; Russkiy Mir; Moral pública; Subjetivación política; https://purl.org/pe-repo/ocde/ford#5.04.03